Estudo eletroquímico de compostos do tipo melen/melofen e alguns de seus complexos - Rodrigues, Dayvison Ribeiro (2014)
Recently there have arisen new compounds of Schiff base type synthesized from the condensation of Meldrum's acid (or its derivatives) with a diamine (ethylenediamine or o-phenylenediamine) providing compounds classified as melens or melophens, which are structural analogues to the classical salens and salophens. The melophens have been used as ligands to form metal complexes analogous to salophens aiming its application in biomimetic catalysis. Herein, we describe the voltammetric electrochemical characterization to four ligands (H2melen, H2Cy2melen, H2melophen and H2Cy2melophen) and two complexes (MnII(Cy2melofen) and NiII(melophen)) on aprotic medium (DMF) using glassy carbon electrode work, and Ag|Ag+ (0,1 mol·L-1 TBAP, 10 mmol AgNO3) as reference electrode. The H2melen and H2Cy2melen behaved similarly showing an irreversible one electron reduction process (1e-). The proposed mechanism for those compounds involves a step dimerization. The H2melophen and H2Cy2melophen demonstrated similar behavior showing two reductions and two irreversible oxidations, where one of the processes is adsorption of reactant and product. The MnII(Cy2melophen) complex showed a single quasi-reversible redox process centered on the metal MnIII/MnII, which involves the transfer of one electron. The NiII(melophen) presented four cases, being a quasi-reversible (1e-) and the others irreversible processes involving a total of 5 electrons. All potentials were corrected across the redox couple of ferrocene (Fc/Fc+), and the effect of addition of acids and bases in the medium is discussed.